Comparison of inpatient and outpatient cardiac rehabilitation following myocardial infarction. (11th May 2022) - Jankowski, P; Topor-Madry, R; Pinkas, J; Gasior, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac rehabilitation (CR) following myocardial infarction (MI) improves prognosis. Models of second phase CR differ across countries. The aim of the study was to compare outcomes in MI survivors participating in outpatient and inpatient CR programmes. Methods: We included all patients hospitalized due to acute MI in Poland between October 2017 and December 2018 (n=96634). Among them 4411 patients were referred to and commenced outpatient CR, whereas 11626 patients started inpatient CR within 30 days following discharge. All the patients were the subject of prospective follow-up. The primary endpoint was defined as death from any cause. Results: The mean follow-up was 332.8±128.1 days. Younger age, male sex, and a cancer in the history were related to higher probability, whereas diabetes, heart failure, chronic kidney disease, chronic obstructive pulmonary disease, ST-elevation myocardial infarction, and myocardial revascularization were related to lower probability of participation in the outpatient CR. Participation in outpatient CR was related to the risk of all-cause mortality both in univariable (hazard ratio [95% confidence intervals] 0.37 [0.26-0.51]) and multivariable analysis (0.53 [0.38-0.74]). Participation in the outpatient CR was also related to the lower risk of death or MI or stroke (0.57 [0.48-0.67] and 0.72 [0.61-0.84]) and a lower risk of death or hospitalization due to cardiovascular reasons: 0.78 (0.73-0.84) and 0.85 (0.80-0.91) for the univariable and multivariable analyses respectively. The analysis of propensity score matched groups confirmed the results. Conclusion: Outpatient CR following MI may be related to improved prognosis compared to the inpatient programme.